1977
DOI: 10.1007/bf00341614
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-typic changes of platelet monoamine oxidase activity in sub-types of schizophrenia

Abstract: Monoamine oxidase (MAO) activity has been measured in the platelets of controls (n = 42) and schizophrenic patients (n = 49) of three subtypes, using beta-phenylethylamine, p-tyramine, and tryptamine as substrates. Characteristic differences of MAO activity were observed between platelets of patients and controls; the differences were substrate-typic: decreased enzyme activity was found with all three substrates in platelets of the parnaoid subtype. With tryptamine, MAO activity was decreased in the platelets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Several groups of investigators believe that schizophrenic patients with auditory hallucinations are more likely than other schizophrenic patients to have decreased platelet M A 0 (Schildkraut et al 1976, Becker & Shaskan 1977, Orsulak et al 1978, Meltzer et al 1980b). Our own research group (Potkin et al 1978) and several others (Carpenter et al 1975, Demisch et al 1977, Sullivan et al 1978b, Landowski 1977, Landowski & Afeltowicz 1977 have found paranoid symptomatology in chronic schizophrenic patients to be associated with low platelet M A 0 activity and to differentiate these patients from other schizophrenic patients. Some overlap probably exists between schizophrenic patients with hallucinations and those with paranoid symptoms.…”
mentioning
confidence: 62%
“…Several groups of investigators believe that schizophrenic patients with auditory hallucinations are more likely than other schizophrenic patients to have decreased platelet M A 0 (Schildkraut et al 1976, Becker & Shaskan 1977, Orsulak et al 1978, Meltzer et al 1980b). Our own research group (Potkin et al 1978) and several others (Carpenter et al 1975, Demisch et al 1977, Sullivan et al 1978b, Landowski 1977, Landowski & Afeltowicz 1977 have found paranoid symptomatology in chronic schizophrenic patients to be associated with low platelet M A 0 activity and to differentiate these patients from other schizophrenic patients. Some overlap probably exists between schizophrenic patients with hallucinations and those with paranoid symptoms.…”
mentioning
confidence: 62%